2014
DOI: 10.3748/wjg.v20.i25.8187
|View full text |Cite
|
Sign up to set email alerts
|

Effect of gastric acid suppressants and prokinetics on peritoneal dialysis-related peritonitis

Abstract: AIM:To investigate the effect of gastric acid suppressants and prokinetics on peritonitis development in peritoneal dialysis (PD) patients. METHODS:This was a single-center, retrospective study. The medical records of 398 PD patients were collected from January 2000 to September 2012 and analyzed to compare patients with at least one episode of peritonitis (peritonitis group, group A) to patients who never had peritonitis (no peritonitis group, group B). All peritonitis episodes were analyzed to compare perito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 29 publications
2
13
0
Order By: Relevance
“…The results of our study appear to support previous reports [ 21 , 22 ], suggesting that any association between treatment with IGAS and peritoneal infections in PD patients may be largely restricted to patients treated with H2A, while the evidence linking treatment with PPI and these infections was much less consistent. At first sight, this difference is difficult to explain, because both types of IGAS appear to carry similar side effects predisposing to infection.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The results of our study appear to support previous reports [ 21 , 22 ], suggesting that any association between treatment with IGAS and peritoneal infections in PD patients may be largely restricted to patients treated with H2A, while the evidence linking treatment with PPI and these infections was much less consistent. At first sight, this difference is difficult to explain, because both types of IGAS appear to carry similar side effects predisposing to infection.…”
Section: Discussionsupporting
confidence: 88%
“…Treatment with IGAS did not make any difference among groups, although stratified analyses disclosed a trends to an association between H2A therapy and infections by enteric microbia. A more recent case-control analysis on 120 patients [ 22 ] suggested an increased incidence of peritonitis (overall), but not of enteric peritonitis, among patients treated with H2A.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Enteric peritonitis may be caused by a change in the composition and function of gut microbiota due to small intestinal bacterial overgrowth (SIBO) and a reduction in the number of butyrate‐producing bacteria, which can reduce microbial translocation, upon GAS use . However, other studies have suggested that GAS intake is not associated with an increased risk of enteric peritonitis . GASs are used commonly in ESRD patients, and the outcome of PD‐related enteric peritonitis is poor, leading to a high prevalence of catheter removal, transfer to permanent haemodialysis and death .…”
Section: What Is Known and Objectivementioning
confidence: 99%
“…21,22 However, other studies have suggested that GAS intake is not associated with an increased risk of enteric peritonitis. 19,[23][24][25] GASs are used commonly in ESRD patients, and the outcome of PD-related enteric peritonitis is poor, leading to a high prevalence of catheter removal, transfer to permanent haemodialysis and death. 26 Hence, it is imperative to ascertain whether GAS intake can increase the risk of enteric peritonitis in these patients.…”
mentioning
confidence: 99%